STEMI: A transitional fossil in MI classification? - (:unkn) unknown (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 2021)
An important task in emergency cardiology is distinguishing patients with acute coronary occlusion (ACO), who will benefit from emergent reperfusion therapy, from those without ongoing myocyte loss who can be managed with medical therapy and for whom potentially harmful invasive interventions can be deferred. The electrocardiogram is critical in this process. Although the ST-segment elevation myocardial infarction (STEMI)/non-STEMI paradigm is well-established, with STEMI representing ACO, its evidence base is poor, and this can have dire consequences. The universally recommended STEMI criteria do not accurately diagnose ACO; in fact, they miss more than one-fourth of the patients with ACO, and also result in a substantial burden of unnecessary catheterization laboratory activations. We here discuss why we believe it is time to change the current STEMI/non-STEMI paradigm. (c) 2021 Elsevier Inc. All rights reserved.
Keywords: Acute coronary syndromes; Coronary occlusion; Electrocardiogram; Non-ST-elevation myocardial infarction; ST-elevation myocardial infarction; ACUTE MYOCARDIAL-INFARCTION; ASSOCIATION TASK-FORCE; ST-SEGMENT ELEVATION; PRACTICE GUIDELINES COMMITTEE; ACUTE CORONARY SYNDROMES; AMERICAN-COLLEGE; ELECTROCARDIOGRAPHIC CRITERIA; ACC/AHA GUIDELINES; EUROPEAN-SOCIETY; CARDIOLOGY